Economic Linkages Across Space. - Overman, H; Rice, P; Venables, A (Taylor and Francis, 2010)
We develop a diagrammatic framework that can be used to study the economic linkagesbetween regions or cities. Hitherto, such linkages have not been the primary focus of eitherthe theoretical or empirical literatures. We show that our general framework can be used tointerpret both the New Economic Geography and Urban Systems literatures to help usunderstand spatial economic linkages. We then extend the theoretical framework to allow usto consider a number of additional issues which may be particularly important for analyzingthe impact of policy. Such policy analysis will also require empirical work to identify thenature of key relationships. In a final section, we consider what the existing empiricalliterature can tell us about these relationships.